Estrutura funcional de Trichoptera (Insecta) ao longo de um gradiente longitudinal em uma bacia hidrográfica do Cerrado - MATHEUS DE BARROS PICOLOTTO (2024)
Objective: This study aimed to evaluate the functional structure and distribution of Trichoptera larvae assemblages along a longitudinal gradient in a watershed within the Cerrado biome. Methods: The study was conducted in 15 streams distributed across the upper (n=4), middle (n=5), and lower (n=6) reaches of the Sucuriú River watershed (Mato Grosso do Sul, Brazil). Limnological variables were measured, and Trichoptera larvae were collected from the streams and identified to the genus level. Functional traits, including body size, body flexibility, feeding habit, respiration, and body shape, were selected and quantified based on available literature using the fuzzy coding technique. To assess the effects of environmental predictors on the functional structure of insects, an RLQ ordination analysis was performed. Results: A total of 750 individuals, distributed across 18 genera and 9 families, were collected. The most frequent genera in the middle and lower reaches were Smicridea (73%) and Oxyethira (11%), while in the upper reaches, the most frequent genera were Nectopsyche (46%) and Smicridea (13%). A segregation was observed between streams in the upper reaches and those in the middle and lower reaches. In the upper reaches, there was a higher proportion of larger organisms (>0.5 cm) and shredders. Conversely, smaller organisms (≤0.5 cm) and filter-feeders were predominant in the middle and lower reaches. Conclusions: The results indicate that local environmental conditions observed in each section of the watershed are reflected in changes in the functional structure of Trichoptera. Therefore, potential anthropogenic disturbances in the watershed may impact the functional diversity of aquatic insects, consequently affecting the dynamics and functioning of these environments. Keywords: Aquatic insects; functional diversity; invertebrates; functional traits.